Effect of Blood Exposure on Push-Out Bond Strength of Four Calcium Silicate Based Cements - Ashofteh Yazdi, Kazem; Bolhari, Behnam; Sabetmoghaddam, Tohid; Meraji, Naghmeh; Kharazifard, Mohammad Javad (Iranian Endodontic Journal, 2017)
Introduction: The purpose of this study was to compare the push-out bond strength of white ProRoot Mineral Trioxide Aggregate (MTA), Biodentine, calcium-enriched mixture (CEM) cement and Endosequence Root Repair Material (ERRM) putty after exposure to blood. Methods and Materials: A total of 96 root dentin slices with a standardized thickness of 1.00±0.05 mm and standardized canal spaces were randomly divided into 4 main experimental groups (n=24) according to the calcium silicate based cement (CSC) used: white ProRoot MTA, CEM Cement, ERRM Putty and Biodentine. Specimens were exposed to whole fresh human blood and then subdivided into two subgroups depending on the exposure time (24 or 72 h). Push-out bond strength was measured using a universal testing machine. Failure modes were examined under a light microscope under ×10 magnification. Data were analyzed using the two-way ANOVA test. Results: Biodentine exhibited the highest values regardless of the exposure time. The lowest push-out strength values were seen in white ProRoot MTA and CEM cement in both post exposure times. After exposure to blood, the push-out bond strength of all materials increased over time. This increase was only statistically significant in white ProRoot MTA and ERRM specimens. The dominant failure mode in all CSCs was the adhesive mode. Conclusion: Biodentine showed the highest values of push-out bond strength and may be better options for situations encountering higher dislocation forces in a short time after cement application. Keywords: Biodentine; Blood; Calcium-Enriched Mixture Cement; Endosequence Root Repair Material; Mineral Trioxide Aggregate